Makna Uang Panaik dalam Pernikahan Suku Bugis-Makassar sebagai Ide Penciptaan Tari Akkulle - Clara Ayu Gita Romantri Riyanto; Rina Martiara (Jurnal Riset Multidisiplin Edukasi, 2025)
The Akkulle dance work is a work inspired by one of the series of traditional wedding processions, namely madduppa botting, which exists in the Bugis-Makassar tribe from South Sulawesi Province. The word Akkulle itself comes from the Bugis-Makassar language which means capable, where when men want to marry women they must be able to work hard, struggle, try and never give up to collect Panaik money. The process of creating the Akkulle dance work refers to the traditional procession or habits of the Bugis-Makassar people in carrying out the wedding procession. The Akkulle dance work departs from several motifs in the paduppa dance and pamanca dance originating from South Sulawesi. Therefore, the creator made the paduppa dance and pamanca dance as basic movements, which were gradually developed by the arranger from the aspects of space, level, and direction with the accompaniment of traditional Makassar music to add to the atmosphere. The arranger uses South Sulawesi regional musical instruments as the basis for the dance accompaniment to maintain the regional atmosphere that will be presented. The Akkulle dance work is a 24-minute dance work, which is divided into four scenes that visualize the Bugis-Makassar traditional wedding procession and the values ​​contained therein. The Bugis-Makassar traditional wedding ceremony is the end of a man's long struggle to collect dowry to propose to his beloved. The Akkulle dance work has become a general view for the wider community regarding the Bugis-Makassar traditional wedding procession.